Butterfly Wings across the Sky: Storytellers Blue Propellers Cascades in the Air—Humbly Humming Sadly Singing - Jernsletten, Kikki (Nordlit, 2004)
storytellers blue propellers cascades in the air humbly humming sadly singing wishing you would hear them as they go !